2022
DOI: 10.3389/fcell.2022.1054365
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum apolipoprotein B level will reduce the bone mineral density and increase the risk of osteopenia or osteoporosis in adults

Abstract: Objective: There is very limited evidence in the NHANES database linking serum apolipoprotein B and lumbar bone mineral density (BMD) in adults aged 20–59 years. There are few studies associating apolipoprotein B concentrations with BMD, and there is some debate about the association between obesity and BMD. Therefore, the purpose of this study was to determine the association between serum apolipoprotein B concentrations and lumbar spine BMD in adults aged 20–59 years and to predict its association with risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…However, in a study in Chinese women, the relationship between TC, LDL-C levels, and lumbar spine BMD was found to be nonlinear, with a negative correlation on the left side of the inflection point and an increase in BMD with an increase in TC and LDL-C on the right side [35]. Zhu et al [36] observed a significant negative correlation between Apo-B concentrations in men and lumbar spine bone density; namely, an increase in Am J Transl Res 2024;16(1):163-178…”
Section: Discussionmentioning
confidence: 98%
“…However, in a study in Chinese women, the relationship between TC, LDL-C levels, and lumbar spine BMD was found to be nonlinear, with a negative correlation on the left side of the inflection point and an increase in BMD with an increase in TC and LDL-C on the right side [35]. Zhu et al [36] observed a significant negative correlation between Apo-B concentrations in men and lumbar spine bone density; namely, an increase in Am J Transl Res 2024;16(1):163-178…”
Section: Discussionmentioning
confidence: 98%
“…Both a negative relationship between total cholesterol and low-density lipoprotein cholesterol concentrations and BMD [153][154][155][156][157][158] and a positive association between high-density lipoprotein cholesterol and BMD [159] have been reported. Other studies, however, found that higher serum high-density lipoprotein cholesterol and apolipoprotein B levels (traditionally viewed as a protective for CVD factor) reduced BMD and may increase the risk of osteoporotic fracture (including HF) independently of traditional risk factors for fractures [160][161][162][163][164][165][166]. Tis may possibly occur by reduction of osteoblast numbers [167] or function via rare adverse genetic variants [168].…”
Section: Prognostic Value Of Ckd and Related Factors For Predictingmentioning
confidence: 99%
“…A review of previous studies found that most studies on bone mineral density have focused on people aged 20 to 59 years. [12][13][14] Adolescents are in a critical growth phase, and bones are in the building phase until the age of 20 years. In contrast, people older than 60 years may have more underlying diseases.…”
Section: Study Populationmentioning
confidence: 99%